KOMPOSISI ASAM LEMAK IKAN NILA (Macrones nemurus) DAN BAUNG (Macrones nemurus) BUDIDAYA - Edison . (Department of Aquatic Product Technology IPB University in collaboration with Masyarakat Pengolahan Hasil Perikanan Indonesia (MPHPI), 2010)
Crude fat and fatty acids composition were examined in red tilapia (Oreochromis niloticus) and Asian redtail catfish (Macrones nemurus) farmed in cage at Kampar River. Two types of lipids were extracted using chloroform:methanol sohxlet extraction. The fatty acid composition were analyzed by gas chromatography (GC). The result showed that the crude lipids in muscle of fishes change according to the age, but did not change by species. The crude lipids in Macrones nemurus were higher than the Oreochromis niloticus, ranging from 3.74-5.82% and 3.89-4.78 recpectively. Furthermore differences acid (omega-9) and palmitic acid. The percentage of fatty acids omega-3 in Macrones nemurus and in Orechromis niloticus, ranging from 4.1-7.8% and 3.4-7.0% respectively, 4.7-11.5% and 5.8-7.2 respectively for fatty acids omega-6.Keywords: composition, farmed freshwater fishes, fatty acids, Macrones nemurus, Oreochromis niloticus.